2020
DOI: 10.1021/acsanm.0c00706
|View full text |Cite
|
Sign up to set email alerts
|

Polarity Control and Nanoscale Optical Characterization of AlGaN-Based Multiple-Quantum-Wells for Ultraviolet C Emitters

Abstract: Optical properties of AlGaN UVC multiple-quantum-wells (MQWs) with nanoscale inverted polarity domains are strongly related to polar surfaces and nanoscale structures. In this work, the impact of pregrowth nitridation of the sapphire substrate on the polarity control of UVC MQW is highlighted, and the optical properties of III- and N-polar domains were distinguished. Nanoscale cathodoluminescence peak separation of more than 30 nm is observed in lateral-polarity-structure (LPS) UVC MQWs, which is ascribed to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…( 7) with R GaN = 6.5 ± 0.3 and R AlN = 7.7 ± 0.4 can be used to correctly estimate the biaxial strain in IIInitrides via Raman spectroscopy. The considerable application potential of the present findings could benefit a broad readership interested in III-nitride-based optoelectronics and power electronics devices [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][85][86][87][88]].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…( 7) with R GaN = 6.5 ± 0.3 and R AlN = 7.7 ± 0.4 can be used to correctly estimate the biaxial strain in IIInitrides via Raman spectroscopy. The considerable application potential of the present findings could benefit a broad readership interested in III-nitride-based optoelectronics and power electronics devices [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][85][86][87][88]].…”
Section: Resultsmentioning
confidence: 99%
“…Research in wide-bandgap III-nitride semiconductors continues to progress rapidly, especially for the materials with bandgap exceeding that of gallium nitride (3.4 eV). Specifically, III-nitride based heterostructures provide new opportunities for a wide range of research and device applications, such as piezotronics and piezophototronics [1], self-powered photoelectrochemical-type photodetectors [2], room-temperature quantum emitters [3], single photon emitters [4][5][6], resonant tunneling diodes [7], highelectron-mobility transistors [8,9], efficient photoelectrocatalysts for solar water splitting [10], multi-wavelength light-emitting diodes (LEDs) [11,12], and deep ultraviolet (DUV)-LEDs [13][14][15][16][17]. AlGaN-based DUV-LEDs represent a sustainable alternative to replace the environmentally harmful conventional mercury lamps [18] and thus, are becoming crucial for many applications such as water purification and/or inactivation of microorganisms, including bacteria, fungi, and viruses [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The carrier-transport properties of N-polar nitride semiconductors demonstrate emission enhancement of light-emitting diodes and other optical devices. [8,9] Previous simulations have shown that the N-polar AlGaN/AlN structure can be assumed to have a higher carrier density than conventional metal-polar AlGaN/GaN electronic devices. [10] In electronic devices, HEMTs using Al-polar AlN require an AlN cap layer owing to their polarization characteristics, making it difficult to reduce the contact resistance.…”
Section: Introductionmentioning
confidence: 99%
“…[19] Higher luminescence intensity was observed in N-polar than in III-polar domains, which can be ascribed to thickness fluctuations in N-polar domains as previously demonstrated by transmission electron microscopy (TEM). [20,21] However, it must be noted that in addition to that, composition fluctuation and strain variation also play critical roles in the carrier localization effect, which has never been investigated before and, thus, requires in-depth investigations, especially from the perspective of nanoscale mapping.…”
Section: Introductionmentioning
confidence: 99%